A new pathway for livelihood improvement and adaptation to climate change: growing vegetables in Hoima, Uganda. Final technical report. - Mwanguhya, Joshua; Kiiza, Annet; Kabakoyo, Elizabeth; Turyahumura, Alex; Recha, Tobias; Vernooy, Ronnie (Bioversity International and the International Center for Tropical Agriculture, 2021)
The crowdsourcing vegetable pilot project was implemented in Hoima, Uganda, from March 2019 to the beginning of 2021, by East-West Seed Knowledge Transfer and the Alliance of Bioversity International and CIAT, in collaboration with the World Vegetable Centre and the National Agricultural Research Organisation of Uganda and notably the Bulindi Zonal Agricultural Research and Development Institute in Hoima. The main objective of this novel collaborative initiative was to support resource-poor farmers to cope better with climate change through increased availability and diversity of climate-smart vegetable varieties. In addition, the pilot project aimed at strengthening farmers’ capacity to make better use of vegetable crop diversity for multiple livelihood purposes, including nutrition and income generation. This report 1) highlights the extent to which the project’s objectives were achieved; 2) assesses, to the extent possible (given the outbreak of Covid-19, which seriously hindered field operations during much of 2020) the project’s positive and negative impacts; 3) assesses to what extent the objectives of the project are consistent with beneficiaries’ requirements and the country’s priorities; and, 4) examines if the project’s benefits will continue after the pilot has ended.